The political information environment in Denmark 2.0 - Blach-Ørsten , Mark; Mayerhöffer, Eva (Politica, 2021)
The article analyzes and discusses recent developments in the political information environment in Denmark, understood as the supply of and demand for political news and political information in a given society. The article focuses on the supply of and demand for (political) news by traditional news media and alternative news media, as offered offline, online and on social media. The article shows that leading traditional news media are still the cornerstone of Danish news consumption, but also that users with lower levels of education and income from outside the Copenhagen area access traditional news outlets less frequently than the rest of the population. For social media, the analysis shows that Facebook remains the dominant social media platform in Denmark. At the same time, only 13 percent of Danish citizens consider “social media” as their most important source of news. Finally, the analysis of the Danish alternative media landscape shows that the monopoly position of traditional news media as a provider of news and views to a wide audience is increasingly challenged by a very heterogeneous group of new online media that includes hyperpartisan media, slow news media and debate-oriented media. The article concludes by discussing how the changes in the political information landscape can affect the democratic dialogue in Denmark.